ทรานสคริปโทมของข้าวพันธุ์พื้นเมืองไทยภายใต้ภาวะเครียดจากความเค็ม - พีรวัธน์ จันทนกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Rice (Oryza sativa L.) has been a staple food source for many Asian countries. The northeastern of Thailand is one of the main regions for high quality rice farming. However, the grain yield obtained from rice grown in this area is quite low due to soil salinity, which affects plant growth, development and fertility. Based on the evaluation of rice seedling responses to salinity stress, ‘Luang Prathan’ rice, one of local Thai rice cultivars, performed salinity tolerance characters. To investigate the mechanisms of salt tolerance, transcriptomes of ‘Luang Prathan’ rice after 0, 3, 6, 12, 24, and 48 hours after salt stress treatment were explored by using 3’-Tag RNA-seq. The differentially expressed gene (DEG) was first detected after 12 hours of stress treatment, which is OsRCI2-5, the gene involving in salt stress signal transduction. After 24 hours of salt stress, OsRMC, a gene responding to salt stress was detected as the significant differentially expressed gene. On the next timing, 48 hours of salt stress, 63 DEGs were detected, most of which were the genes with the stress protection functions. The result of gene co-expression network derived from partial dynamical correlation coefficient of 64 DEGs shows co-expression of OsRCI2-5 and OsRMC with stress responsive regulator gene, transcription factor and ubiquitin ligase enzyme. Moreover, in salinity condition, OsRMC might plays a role in the induction of gene involve with plant defense response. Based on the validation of these expressed genesby qRT-PCR, OsRCI2-5 and OsRMC are plant salt stress responsive genes and involving in salt tolerance mechanism in ‘Luang Prathan’ rice.